The Role of Catalase C262T Gene Polymorphism in the Susceptibility and Survival of Cancers - Wang, Cheng-Di (Sci Rep, 2016)
Catalase (CAT), one antioxidant enzyme, may provide resistance against many diseases. Many previous studies reported predictive and prognostic values of CAT C262T polymorphism in cancers, with divergent results. This study aimed to summarize the overall relationships between CAT C262T polymorphism and cancer risk or survival. A total of 27 eligible publications were included in susceptibility analysis, while 8 publications contained survival outcomes. The results revealed significant relationship between CAT C262T polymorphism and cancer risk(TT + CT vs CC: OR = 1.05, 95%CI = 1.00–1.10, P = 0.036), subgroup analyses indicated the CAT C262T polymorphism was significantly correlated with an increased risk for prostate cancer (TT vs CC + CT: OR = 1.43, 95%CI = 1.20–1.70, P < 0.001) and increased risk among Caucasians (TT vs CC + CT: OR = 1.19, 95%CI = 1.09–1.31, P < 0.001), while no associations between the polymorphism and Asian or mixed population were established. In the survival analysis, no interactions were identified between this polymorphism and cancer survival (TT + CT vs CC: HR = 1.37, 95%CI = 0.70–2.70, P = 0.36). In conclusion, the CAT C262T polymorphismmay be a candidate markerfor cancer risk with type-specific and population-specific effects but not a fine prognostic factor for cancer survival.